The slime hand illusion: Nonproprioceptive ownership distortion specific to the skin region. (November 2022) - Kodaka, Kenri; Sato, Yutaro; Imai, Kento
The "slime hand illusion" is a simple and robust technique that uses mirror-visual feedback to produce a nonproprioceptive ownership distortion. The illusion can be easily evoked by the participant watching the experimenter pinching and pulling a chunk of slime in a mirror while the participant's hand, hidden behind the mirror, is similarly manipulated. This procedure produces a feeling of one of their fingers or the skin of their whole hand being stretched or deformed in a similar way to the visible slime. A public experiment found that more than 90% of participants reported a strong sense of skin or finger stretching. This report details a laboratory experiment performed to characterize the mechanisms behind the illusion more robustly. It reproduced this result and found that participants experienced a drift in their sense of skin location of approximately 30 cm on average, which is beyond the conventionally accepted range of proprioceptive drift.